Economic Dependence Relationship and Spatial Stratified Heterogeneity in the Eastern Coastal Economic Belt of China - Xianbo Wu; Xiaofeng Hui (Complexity)
In this paper, the method of mutual information is used to study the economic dependence among the provinces in Chinaʼs Eastern Coastal Economic Belt from 2015 to 2020, and the core structure of the dependence is depicted. The results show that, first of all, there is a wide range of economic dependence among the provinces in the Eastern Coastal Economic Belt, and the dependence changes with the different states of economic development. Secondly, the phenomenon of geographical clustering is not obvious. Most provinces maintain a strong economic dependence relationship with the economically developed provinces, and this dependence relationship is relatively stable, while the economically underdeveloped provinces are often on the edge of the dependence structure. Finally, the economically developed provinces maintain strong economic dependence with each other, such as Jiangsu (No. 7), Shandong (No. 9), and Zhejiang (No. 12), and Beijing (No. 1), Guangdong (No. 3), and Shanghai (No. 10). However, the former three provinces are more in the core position of this structure, that is, the other provinces maintain the stronger dependence relationship with these three provinces.